If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + -1(p + 4) = -2(2p + -1) + 10 Reorder the terms: 7p + -1(4 + p) = -2(2p + -1) + 10 7p + (4 * -1 + p * -1) = -2(2p + -1) + 10 7p + (-4 + -1p) = -2(2p + -1) + 10 Reorder the terms: -4 + 7p + -1p = -2(2p + -1) + 10 Combine like terms: 7p + -1p = 6p -4 + 6p = -2(2p + -1) + 10 Reorder the terms: -4 + 6p = -2(-1 + 2p) + 10 -4 + 6p = (-1 * -2 + 2p * -2) + 10 -4 + 6p = (2 + -4p) + 10 Reorder the terms: -4 + 6p = 2 + 10 + -4p Combine like terms: 2 + 10 = 12 -4 + 6p = 12 + -4p Solving -4 + 6p = 12 + -4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '4p' to each side of the equation. -4 + 6p + 4p = 12 + -4p + 4p Combine like terms: 6p + 4p = 10p -4 + 10p = 12 + -4p + 4p Combine like terms: -4p + 4p = 0 -4 + 10p = 12 + 0 -4 + 10p = 12 Add '4' to each side of the equation. -4 + 4 + 10p = 12 + 4 Combine like terms: -4 + 4 = 0 0 + 10p = 12 + 4 10p = 12 + 4 Combine like terms: 12 + 4 = 16 10p = 16 Divide each side by '10'. p = 1.6 Simplifying p = 1.6
| 3-x+4x=6 | | 5+7x-x=71 | | X+1.5x= | | 7x-7y=5solvey | | 4nsquared+4n-168=0 | | k=gd | | 21x+1=4 | | 6m+6(6m-3)=108 | | 10-5t=6t-23 | | f(x)=ln(e^2x) | | y+3=.5(x-4) | | 16y^8= | | 3x+84=75 | | 72x+9y=18 | | 13x=2(5x+3) | | 9(x+7)+10=11x-2(x-3) | | 24-2x=14x-21 | | 3x^3+8x=420 | | 5b^4=134 | | 5+3(3x-5)=5-4(2x+1) | | 3x^2+8x=420 | | 2cosx=1-sinx | | f(x)=x^3-3x^2-9x+12 | | 0.8(x+300)=0.84x-56 | | 14-x^4= | | 2cos^2x+2cosx-1=0 | | 0.87y+2=y-0.6 | | 23.4=7.8*n | | (k-4)x^2-3kx-k-1=0 | | 6*n=22.8 | | 14+4096= | | y=3x^2-2x-1 |